1994
DOI: 10.1161/01.cir.89.6.2780
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in coronary artery vascular reactivity of hypertensive Ren-2 transgenic rats.

Abstract: Ren-2 transgenic rats develop fulminant hypertension that is associated with a selective decrease in endothelium-dependent contractions in response to L-NAME, whereas endothelium-dependent relaxations in response to acetylcholine as well as smooth muscle function remain unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Considering other models of hypertension, isolated coronary arteries from hypertensive Ren-2 transgenic rats relax normally in response to acetylcholine, but basal NO dilatory function is reduced in comparison with controls [32]. Additionally, small coronary arteries from pigs with a renal model of hypertension display normal endothelium-dependent relaxations in response to bradykinin, substance P and 5-HT [33], which demonstrates that abnormal endothelium-mediated responses are not a consistent feature of the coronary vasculature in hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…Considering other models of hypertension, isolated coronary arteries from hypertensive Ren-2 transgenic rats relax normally in response to acetylcholine, but basal NO dilatory function is reduced in comparison with controls [32]. Additionally, small coronary arteries from pigs with a renal model of hypertension display normal endothelium-dependent relaxations in response to bradykinin, substance P and 5-HT [33], which demonstrates that abnormal endothelium-mediated responses are not a consistent feature of the coronary vasculature in hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…Endothelium-dependent relaxation in response to acetylcholine has been reported to be impaired in one study of aorta. 31 In contrast, responses to endothelium-dependent agonists in TGR(mRen2)27 were not impaired in another study of aorta 32 and studies of coronary arteries 33 and the mesenteric circulation. 34 Responses to endothelium-dependent agonists were enhanced in the renal circulation of TGR(mRen2)27 compared with nontransgenic controls.…”
Section: Vascular Responses In Control and R؉/a؉ Micementioning
confidence: 89%
“…22 In contrast to baseline effects, acetylcholine (ACh)-stimulated dilation of the coronary circulation was similar in normotensive and hypertensive animals, and was abolished in Hypertension, NO, and coronary endothelium Dovepress submit your manuscript | www.dovepress.com Dovepress both groups by L-NAME, suggesting stimulated NO release and/or bioavailability may be unaltered by hypertension in this vascular bed. 50 Further analysis revealed, however, that the relationship between CVR and NO production is altered in SHR hearts so a greater amount of NO production occurs despite a persistently much higher CVR than in WKY controls. 18 Furthermore, inhibition of eNOS with l-arginine analogues also blunts constrictory responses in the majority of the coronary perfusion studies in hypertensive hearts, 19,21 suggesting that NO is contributing to constrictory responses in the hypertensive coronary vascular bed likely via its destruction by superoxide and the consequent effects of reactive species formed.…”
Section: Nitric Oxide Bioavailability In the Control Of Coronary Hemomentioning
confidence: 96%
“…Indeed, in general, endothelium-mediated (drug-and shear stress-stimulated) dilation of isolated coronary arteries is reduced in hypertensive humans 11,[53][54][55][56][57] and animals, 19,21,32,36,45,51,52,[58][59][60][61][62] while the endothelium-independent vasodilatory responses to sodium nitroprusside and adenosine are often unaltered. 21,32,45,55,63 There are exceptions to these general observations 18,33,50,[63][64][65][66] and the vessel type (conduit vs resistance artery), 45,57 the mode of precontraction, 33 and the vasodilator protocol 45,56,61,67 or eliminated 58,68,69 by inhibitors of eNOS in isolated coronary vessels from hypertensive animals, suggesting that NO remains an important component of vascular function even when its bioavailability is reduced in hypertension. In isolated pressurized coronary microvessels it was observed that removal of the endothelium increased the amount of myogenic constriction to a greater extent in SHR than in WKY over a wide pressure range.…”
Section: Nitric Oxide-mediated Vasomotor Function Of Isolated Coronarmentioning
confidence: 97%